2008
DOI: 10.1103/physrevb.78.134516
|View full text |Cite
|
Sign up to set email alerts
|

Indications for intrinsic superconductivity in highly oriented pyrolytic graphite

Abstract: High-resolution magnetoresistance data in highly oriented pyrolytic graphite thin samples manifest nonhomogenous superconductivity with critical temperature T c ϳ 25 K and higher temperature. Our claim is based mainly in the observation of anomalous hysteresis loops of resistance versus magnetic field that cannot be assigned to magnetic irreversibility but indicates the existence of Josephson-coupled superconducting grains. In addition we observe quantum resonances that can be assigned to Andreev reflections a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
45
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 34 publications
17
45
2
Order By: Relevance
“…Recently done study of the behavior of the MR of multigraphene samples suggests the existence of granular superconductivity [6]. The main experimental evidence comes from the anomalous irreversible behavior of the MR, which appears compatible with Josephson-coupled superconducting grains [6]. We note that Bi, as graphite, has a low density, low effective mass of carriers and huge values of the electron mean free path [24,25].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently done study of the behavior of the MR of multigraphene samples suggests the existence of granular superconductivity [6]. The main experimental evidence comes from the anomalous irreversible behavior of the MR, which appears compatible with Josephson-coupled superconducting grains [6]. We note that Bi, as graphite, has a low density, low effective mass of carriers and huge values of the electron mean free path [24,25].…”
Section: Figurementioning
confidence: 99%
“…The possibility of superconductivity in graphite has been discussed in recent years, see Refs. [7,6] for further reading.…”
Section: Figurementioning
confidence: 99%
“…To date, a significant number of indirect experiments indicating the existence of a superconducting state up to room temperature in graphite-based compounds have been reported [8][9][10][11][12]. The main problem of these indirect observations lies in the fact that the superconducting regions occupy only a small areas of carbon materials, and for this reason, the observable effects of superconductivity are negligible in bulk samples [9]. Evidence for superconductivity in graphite lamellae at temperatures above 150 K has been demonstrated in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although signs of granular superconductivity in the electrical resistance of graphite samples with electrodes on the main surface (usually on the top graphene layer) have been recognized in earlier studies [39,40], if we could contact directly the edges of the interfaces found in graphite samples we expect to observe more clear signs of Josephson or granular superconducting behavior in the transport measurements. As it became evident from the results shown in Fig.…”
Section: Contacting the Interface Edges In Tem Lamellaementioning
confidence: 94%